S-50-3: MICROSAMPLING BASED MASS SPECTROMETRY FOR QUANTIFICATION OF ANGIOTENSIN PEPTIDES IN THE RENIN ANGIOTENSIN ALDOSTERONE SYSTEM. (January 2023) - Bernieh, Dennis; Lane, Dan; Gill, Henry; Jones, Don; Gupta, Pankaj
Abstract : Objective: Hypertension is the leading risk factor of premature death globally, affecting around 1.3 billion people. The canonical renin angiotensin aldosterone system (RAAS) has been extensively studied and methods are available for use clinically to assess hypertension. The non-canonical axis of the RAAS (consists of angiotensin 1Ξ7, angiotensin 1Ξ9, angiotensin converting enzyme 2 and alamandine) counteract the effects of the canonical pathway. This reveals their role as potential therapeutic targets for cardiovascular disease, but it has not been studied in detail in the clinical or research setting due to the difficulty in measuring its components owing to instability. Furthermore, the functional balance between the two arms of RAAS has not been fully understood. These limitations can be overcome by using dried microsampling, which provides better sample stability. Microsampling requires just a micro blood volume (<30 μL) from a finger prick collected on a card. It is minimally invasive, cheap, and easy to collect by patients. Design: A microsampling based liquid chromatography coupled with triple quadrupole mass spectrometry (LCMS/MS assay) was developed and optimised to simultaneously quantify 10 peptides (angiotensin II, Ang III, Ang IV, ACE2, Ang 1Ξ5, Ang 1Ξ7, Ang 1Ξ9, Ang 1Ξ12, Alamandine and Ang A) in the RAAS pathway. Methods: For the preparation of calibration samples, 30 μL of bovine serum albumin (BSA) was spiked with the 10 peptides standards, spotted on a card, dried and extracted by solid phase extraction using their respective internal standards. Chromatographic analyses were performed on an Acquity C18 Premier peptide column using gradient elution with a run time of 8 min. Identification was carried out using electrospray ionisation (positive) on a Waters Xevo TQXS triple quadrupole mass spectrometer. The developed assay is currently undergoing validation in line with international guidelines. Results: The method shows good linearity. The accuracy (relative error) and precision (coefficient of variation) values were within the pre-defined limits of ≧15% at all tested concentrations for the peptides. The assay sensitivity was sufficient to detect the peptides in dried blood spot samples. Conclusion: The microsampling based LCMS/MS assay development was successful and following completion of validation has the potential to quantify the circulating levels of these vasoactive peptides in patients with hypertension. This has been achieved, for the first time to the best of our knowledge on the entire RAAS pathway. This microsampling based proteomics assay could be used to study patients with hypertension in both research and clinical settings.